1993
DOI: 10.1084/jem.177.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the antigen presenting cell function(s) of pulmonary dendritic cells in vivo by resident alveolar macrophages.

Abstract: Sllnllnal~Class II major histocompatibility complex (Ia)-bearing dendritic cells (DC) from airway epithelium and lung parenchyma express low-moderate antigen presenting cell (APC) activity when freshly isolated. However, this function is markedly upregulated during overnight culture in a manner analogous to epidermal Langerhans cells. The in vitro "maturation" process is inhibited by coculture with pulmonary alveolar macrophages (PAM) across a semipermeable membrane, and the degree of inhibition achieved can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
349
2
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(373 citation statements)
references
References 40 publications
17
349
2
3
Order By: Relevance
“…Whereas DC activate T cells and thereby promote inflammation, pulmonary M⌽ suppress these processes (20,21,37,43). It has therefore been suggested that the balance of these two cell types influences the progression of lung inflammation, such as asthma (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas DC activate T cells and thereby promote inflammation, pulmonary M⌽ suppress these processes (20,21,37,43). It has therefore been suggested that the balance of these two cell types influences the progression of lung inflammation, such as asthma (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that pMU might be suppressor MU with a role in the maintenance of peripheral tolerance upon scavenging self antigen derived from for instance apoptotic cells. Indeed, the anti-inflammatory and immune-suppressive capacities of resident MU were also found in other tissue MU, such as murine alveolar MU [18,19] and human intestinal MU [20].…”
Section: Mu2 and Pmu Show Hampered T Cell-stimulatory Capacitymentioning
confidence: 91%
“…This suppressive effect was mediated directly, by the secretion of NO, IL-10 and/or prostaglandin E 2 (PGE 2 ) (reviewed in Ref. [31]), or indirectly, by inhibition of pulmonary dendritic cell maturation by secretion of NO and TNF-a [32].…”
Section: Infectious Agents and The Hygiene Hypothesismentioning
confidence: 99%